PENGARUH PENERAPAN MODEL PEMBELAJARAN SENTRA ALAM TERHADAP PENINGKATAN KEMAMPUAN KREATIVITAS DAN KOLASE PADA ANAK USIA - Wiwik Sulistyawati; Rudy Sumiharsono; Kustyowati Kustyowati (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2022)
This type of research is causal quantitative research. Determination of the research area is done using purposive sampling area techniques. In this study, the method of determining respondents was population reseach. The methods used by the author in data collection in this study are 1) Observation (observation), 2) Interview (interview), and 3) Documentation. Pre-research includes trials of research instruments of both validity and reliability. While post-research is a test conducted to find out the results of research that will determine the acceptance or rejection of a research hypothesis. From the results of this study the authors can conclude that the results on the first hypothesis test p value of 3.146 means p > 0.05, in the second hypothesis test p value of 5,160 means p > 0.05 and in the third hypothesis test p value of 36.764 means p > f table then in all tests the null hypothesis is rejected. Therefore, the results of the study are a) there is an influence on the application of the natural center defense model on the improvement of creativity skills in children aged 5 - 6 in kindergarten Labschool Universtas PGRI Argopuro Jember even semester of the School Year 2020/2021, b) there is an influence on the application of the natural center defense model on collage in children usi 5 - 6 in kindergarten Labschool Universtas PGRI Argopuro Jember even semester of the School Year 2020/2021, c) There is an influence on the Application of Natural Center Learning Model on the improvement of Creativity and increased collage ability together in children aged 5 - 6 in kindergarten Labschool Universtas PGRI Argopuro Jember.